STRATEGI PEMBERANTASAN KORUPSI MELALUI PENDEKATAN POLITIK HUKUM, PENEGAKAN HUKUM DAN BUDAYA HUKUM - Yusyanti, Diana (E-Journal Widya Yustisia, 2018)
The practice of criminal acts of corruption that happens increasingly sophisticated Indonesia, systematic and widespread in all walks of life who have an impact on the amount of the financial loss to the State. Various laws and regulations that have attempted to eradicate the corruption that Law Number 31 of 1999 Jo Act No. 20 of 2001 even Government has ratified several articles of the United Nations Convention Against Corruption (UNCAC) 2003 through law No. 7 Th 2006. But so far this is still unable to put in place and are effective in eradicating corruption. The purpose of this writing is to know the: (1) the role of political and law-enforcement efforts in the eradication of criminal acts of corruption, (2) consistency of law enforcement efforts in the eradication of criminal acts of corruption that could influence the attitude of the law enforcement apparatus in legal norms and behaviour or attitude in the exercise of his profession in the follow-up process of the rule of law, (3) the role of the Legal culture in helping reduce and even eradicate behaviour a criminal offence of corruption.The methods used is the law normative approach and descriptive analytical data based on primary law materials, secondary and tertiary. It can be concluded that: (1) legal corruption eradication strategy should press, hold or curb corruption by giving heavy sanctions, improved coordination among law enforcement agencies and develop a culture of shame against corruption.